Comparative Molecular Microbial Ecology of the Spring Haptophyte Bloom in a Greenland Arctic Oligosaline Lake - Theroux, Susanna; Huang, Yongsong; Amaral-Zettler, Linda (Frontiers in Microbiology, 2012)
The Arctic is highly sensitive to increasing global temperatures and is projected to experience dramatic ecological shifts in the next few decades. Oligosaline lakes are common in arctic regions where evaporation surpasses precipitation, however these extreme microbial communities are poorly characterized. Many oligosaline lakes, in contrast to freshwater ones, experience annual blooms of haptophyte algae that generate valuable alkenone biomarker records that can be used for paleoclimate reconstruction. These haptophyte algae are globally important, and globally distributed, aquatic phototrophs yet their presence in microbial molecular surveys is scarce. To target haptophytes in a molecular survey, we compared microbial community structure during two haptophyte bloom events in an arctic oligosaline lake, Lake BrayaSø in southwestern Greenland, using high-throughput pyrotag sequencing. Our comparison of two annual bloom events yielded surprisingly low taxon overlap, only 13% for bacterial and 26% for eukaryotic communities, which indicates significant annual variation in the underlying microbial populations. Both the bacterial and eukaryotic communities strongly resembled high-altitude and high latitude freshwater environments. In spite of high alkenone concentrations in the water column, and corresponding high haptophyte rRNA gene copy numbers, haptophyte pyrotag sequences were not the most abundant eukaryotic tag, suggesting that sequencing biases obscured relative abundance data. With over 170 haptophyte tag sequences, we observed only one haptophyte algal Operational Taxonomic Unit, a prerequisite for accurate paleoclimate reconstruction from the lake sediments. Our study is the first to examine microbial diversity in a Greenland lake using next generation sequencing and the first to target an extreme haptophyte bloom event. Our results provide a context for future explorations of aquatic ecology in the warming arctic.